ANALISA PRODUKTIVITAS MENGGUNAKAN MODEL APC UNTUK MENINGKATKAN PROFITABILITAS DI PT. DIANTRIJAYA UTAMA MUKTI - putrihadiningrum, Devika; Husada, Alvian (MERDEKA : Jurnal Ilmiah Multidisiplin, 2024)
This research aims to determine productivity values based on measurements using the APC model, identify factors that can enhance organizational productivity using the APC, and provide improvement suggestions for the company by measuring productivity to increase the company's profitability using the APC model. This research is a field study with quantitative data obtained from the company's fi-nancial and operational reports from 2021 to 2023. The analysis measured changes in productivity using the APC model. The results showed that the productivity index calculated using the APC model comprised: labor 110%, materials 109%, en-ergy 104%, and capital 115%. In this case, the researcher recommends the APC method approach for Diantrijaya Utama Mukti Ltd. because this method can be analyzed more comprehensively and deeply, focusing on the long-term improve-ments needed by the company. Efforts to enhance the company's productivity using the APC model include increasing effectiveness in labor and materials. Recommendations for the company to improve productivity and profitability using the APC model include hiring local labor, improving the warehousing system, se-lecting energy-efficient machines, and seeking alternative funding sources..